Role of the Magnitude of Digital Adaptability in Sustainability of Food and Beverage Small Enterprises Competitiveness - Bambang Dwi Suseno; . Basrowi (HighTech and Innovation Journal, 2023)
This study aimed to (1) determine and (2) improve the sustainability of competitiveness for the food and beverage business. This was achieved through causal studies, which involved determining causal relationships between variables. The study population was selected using a purposive sampling technique with a focus on small food and beverage entrepreneurs, and the data retrieved were analyzed using both quantitative and qualitative methods. Moreover, IBM SPSS AMOS 21 (Moment Structure Analysis) tool was used for the descriptive analysis as well as to test models and hypotheses. The results showed that stakeholder engagement had a positive and significant influence on the magnitude of digital adaptability and costless signaling. It was further noted that the magnitude of digital adaptability and costless signaling had the same effect on sustainability. A similar relationship was established between costless signaling and the magnitude of digital adaptability. These results proved that stakeholder engagement has a significant effect on cost-effective signaling and the magnitude of digital adaptability. Costless signaling has a significant effect on the magnitude of digital adaptability and sustainability of small food and beverage enterprises performance. The novelty of this study lies in the influence of stakeholder engagement on the magnitude of digital adaptability, which can be used to increase the sustainability and performance of food and beverage small enterprises.